Evaluating 3-D positioning infrastructure quality and utilization: The potential improvement with multi-GNSS methods - Atunggal, Dedi; Widjajanti, Nurrohmat; Aditya, Trias (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
This article evaluates the quality of the national 3-D positioning infrastructure using multi-criteria decision making (MCDM) to simulate the potential application of multi-GNSS method. The MCDM evaluation used coverage and availability of Indonesia Continuous Operating Reference System (INACORS) services, distribution of survey pillars, and accuracy of height determination using the Indonesian Geoid Model (INAGEOID). The term multi-GNSS method refers to the utilization of PPP method as a complement to the conventional differential GNSS method for the production of mapping control points. The results of this evaluation were complemented by a questionnaire analysis on the utilization of positioning infrastructure by respondents from various professional backgrounds. The MCDM evaluation results showed that Java had nearly 100% good or excellent 3-D positioning infrastructure quality. Other regions in Indonesia still had significant areas of average, fair, or even poor quality. The questionnaire results showed that many users have faced some problems in areas with fair or poor infrastructure quality. The application of multi-GNSS method can contribute to reduce up to half of the area with fair and poor positioning infrastructure quality.